How to Explain the Social Skills Development of Pupils? - Fanchini, Agathe (International Journal of Technology and Inclusive Education, 2016)
Differences of achievement in school, traditionally studied by researchers in Education, can be analyzed in terms of skills and especially social skills. This scientific field is under construction but social skills are becoming a compulsory notion for actors of the school system and for Educational Sciences. Through a multidisciplinary approach, this article proposes to study the determinants of social skills using social and educational indicators widely borrowed into the explanation of the differences of achievement models, with associated self-image, neuroticism and relationship with school measures. Indeed, these three dimensions are involved in the socialization and development of student skills. A reliable analytic tool of social skills (in a sample of 855 students from 7 to 12 years) enables us to understand for example girls' success at school or the weight of the self-image in the development of social interpersonal and intra-individual skills. The results which explain determinants of social skills (self-explanatory success) allow opening the debate on the differences in academic achievement in school and redesign the classic pattern of the direct link between the characteristics and achievement, by intermediate effect of social skills.